Evaluation of General Public’s Knowledge and Perception of Appropriate Antibiotics use in Salem District - Radhakrishnan, Rahul; Balasundaram, Jaykar; Balasubramaniam, Arul; Gunasekaran, Guru (Indian Journal of Pharmacy Practice)
Objective: The objective of this study was to evaluate the general population’s current knowledge, expectations, and usage of antibiotic in Salem district of Tamil Nadu. Method: The survey was developed based on previous researches. The survey was initially developed in English and then translated to Tamil. The survey gathered demographic information and collected data on knowledge, preferences, expectations, and antibiotic usage in population of Salem district. Results: Survey has 142 participants in which 92 responded well representing a 65% response rate. 63.9% of respondents believed that they could stop taking antibiotics if their symptoms of infection improved. Around half of the population (43.5%) believed antibiotics are effective for most of the colds and over a half of respondents (55.4) stated that, they prefer to keep antibiotics at home for emergencies. Approximately a one third of respondent (36.1%) would give their antibiotics to a family member if they caught an infection, 14.2% of respondents identified that, and they have bought an antibiotic from community pharmacies at Salem without a prescription. Conclusion: The study showed that the population in Salem has a number of misconceptions relating to appropriate antibiotic use, particularly relating to use of antibiotics for treatment of viral infections. As antibiotics are widely used in Salem as well as India, proper education should be given about rational use of antibiotics to the public.
Keywords: Rational Use; Antibiotics; Prospective study; Public Knowledge; Appropriate